Influence of N2 Flow Rate on Mechanical and Tribological Properties of TAlN Coatings Deposited on 300M Substrate and Nitrocarburized Layer - Shiwei Zuo; Qinghua Li; Zhehang Fan; Xiaoyong Tao; Xiangjie Wang; Hui Xie; Qianqian Shen; Tianshi Jia; Hongyan Wu (Lubricants)
This study systematically investigates the influence of nitrogen (N2) flow rates and nitrocarburized (PNC) interlayers on the mechanical and tribological properties of TiAlN coatings deposited on 300M steel substrates via magnetron sputtering. The coatings were fabricated under three N2 flow rates (30, 90, and 150 sccm), with microstructure evolution, elemental composition, and phase transitions analyzed using SEM, EDS, AFM, and XRD. The results indicate that the PNC/TiAlN composite coatings exhibited superior interfacial adhesion and load-bearing capacity compared to standalone TiAlN coatings, attributed to the graded hardness transition and stress distribution optimization at the coating–substrate interface. Nanoindentation tests revealed enhanced hardness and elastic modulus in PNC/TiAlN systems under high N2 flow conditions. Tribological evaluations demonstrated that the composite coatings achieved lower specific wear rates (25.23 × 10−8 mm3·N−1·m−1) under 7.3 N, outperforming monolithic TiAlN coatings by mitigating abrasive wear and delamination. The synergy between N2 flow modulation and nitrocarburizing pretreatment effectively optimized coating–substrate compatibility, establishing a robust framework for designing wear-resistant TiAlN coatings in extreme service environments. This work provides critical insights into tailoring PVD coating architectures for aerospace and heavy-load applications.